The Effects of Alcohol on the Emotional Displays of Whites in Interracial Groups - Fairbairn, Catharine E. (Emotion, 2013)
Discomfort during interracial interactions is common among Whites in the U.S. and is linked to avoidance of interracial encounters. While the negative consequences of interracial discomfort are well-documented, understanding of its causes is still incomplete. Alcohol consumption has been shown to decrease negative emotions caused by self-presentational concern but increase negative emotions associated with racial prejudice. Using novel behavioral-expressive measures of emotion, we examined the impact of alcohol on displays of discomfort among 92 White individuals interacting in all-White or interracial groups. We used the Facial Action Coding System and comprehensive content-free speech analyses to examine affective and behavioral dynamics during these 36-minute exchanges (7.9 million frames of video data). Among Whites consuming nonalcoholic beverages, those assigned to interracial groups evidenced more facial and speech displays of discomfort than those in all-White groups. In contrast, among intoxicated Whites there were no differences in displays of discomfort between interracial and all-White groups. Results highlight the central role of self-presentational concerns in interracial discomfort and offer new directions for applying theory and methods from emotion science to the examination of intergroup relations.